Quantification of trace element atmospheric deposition fluxes to the Atlantic Ocean (>40°N; GEOVIDE, GEOTRACES GA01) during spring 2014. (January 2017) - Shelley, Rachel U.; Roca-Martí, Montserrat; Castrillejo, Maxi; Masqué, Pere; Landing, William M.; Planquette, Hélène; Sarthou, Géraldine
Abstract: Atmospheric deposition is an important input route of trace elements (TEs) to the global ocean. As atmospheric inputs impact phytoplankton community health and dynamics, atmospheric TE fluxes, and in particular atmospheric iron fluxes, are a key component of marine biogeochemical models. Trace element concentrations were determined in dry (aerosols) and wet (precipitation) deposition samples from the North Atlantic, north of 40°N, during the GEOVIDE cruise (GEOTRACES cruise GA01) in May/June 2014. Atmospheric aerosol loading in the study region was low (~ 2–500 ng m -3 ) throughout the cruise, as inferred from the very low aerosol Ti concentrations determined (0.0084–1.9 ng m -3 ). Wet deposition appeared to be of roughly equal or greater importance than dry deposition to the total depositional flux of TEs, which is consistent with other regions of the Atlantic Ocean outside of the influence of the Saharan plume. It can be challenging to convert aerosol chemical composition data into reliable flux estimates, due to the uncertainties associated with the parameterisation of dry deposition velocity, and precipitation rate. Therefore, the goal of this study was to compare TE flux estimates derived from two different techniques: (1) the traditional approach of summed wet and dry deposition TE fluxes, using concentration data, precipitation rates, and dry deposition velocities and, (2) using the inventory of the cosmogenic radioisotope beryllium-7 ( 7 Be) in the upper ocean as a proxy for atmospheric deposition. These two approaches yielded TE flux estimates that were in excellent agreement (within one standard deviation) for about half of the TEs under investigation. However, for the remaining TEs differences between the flux estimates ranged from two to forty times, with the traditional approach generally being the higher of the two estimates. Therefore, factors that may contribute to this variation, such as differences in the timescale of integration and selection of representative deposition velocities and precipitation rates, are discussed. Our results suggest that the 7 Be approach continues to show promise in this application, particularly in regions where precipitation samples cannot be routinely collected. Highlights: Atmospheric deposition of trace elements was low north of 40°N in May/June 2014. The radioisotope 7 Be was used as a proxy for atmospheric deposition. Flux estimates from (1) wet plus dry deposition; (2) the seawater inventory of 7 Be. Similar flux values for some elements, but large differences for others.